Gait analysis parameters of healthy human subjects with asymmetric loads. Issue 8 (10th June 2016) - Berceanu, C.; Marghitu, D.B.; Gudavalli, M.R.; Raju, P.K.; Vikas, Y.
Abstract : This article focuses on the analysis of gait parameters, ground reaction forces (GRF), and motion signals, for the various asymmetric loads carried by healthy human subjects during walking. Eight asymptomatic human volunteers were enrolled in this study. They were asked to walk, at self-selected pace, with various weights ranging from 0 to 11.33 kg (25 lbs) in 2.26 kg (5 lbs) increments, in one hand on a wooden area equipped with a force platform. Moreover, motion data were recorded from lumbar L1 vertebrae at a frequency of 120 Hz. Three trials of data have been recorded for each subject. In order to quantify the effect of increasing loads on the GRF we define the compression area, restitution area, and coefficient of restitution (COR) for GRF curves. We observe an increase in the compression area with respect to the load and almost constant values for the COR. For motion signals analysis we employ wavelet theory. The signals obtained from the lumbar L1 sensor of the spine vertebrae show a decrease in the wavelet detail energy, for the levels 3, 4, and 5, with respect to increasing loads.